Critical test with Ruelene 8-DP against gastrointestinal helminths in cattle - Costa, Hélio Martins de A.; Freitas, Moacyr G.; Guimarães, Marcos Pezzi (Pesquisa Agropecuaria Brasileira, 2014)
The authors conducted a critical test with Ruelene 8-DP, a new Dow Chemical formulation for control of gastrointestinal helminths in cattle. Twenty-four calves were divided into four groups and treated as follows: group A calves received 10 ml/50 kg b.w. by the "pour-on" method; group B calves received 30 ml/50 kg by "pour-on"; group C calves received 25 ml/50 kg by oral administration; and group D was maintained as control. These dosages correspond to 10, 48 and 40 mg of active ingredient per kg of animal weight. The results are summarized as follows: a) The "pour-on" dose to 16 mg/kg was followed by a small reduction in the number of eggs p.g.f. Of the number of worms eliminated: 29.2% were Haemonchus sp.; 0.8% Cooperia sp.; 9.1% Bunostomum phlebotomum; and 0.4% Oesophagostomum radiatum. b) The "pour-on" dose 48 mg/kg resulted in a better reduction to the number of eggs p.g.f. Of the worms eliminated: 51.5% were Haemonchus sp.; 16.7% Cooperia sp.; 12.0% Trichostrongylus axei; 13.0% Bunostomum phlebotomum; 28.7% Oesophagostomum radiatum. c) The best results were obtained with the oral dose of 40 mg/kg. The number of eggs p.g.f. decreased 96%. The worms eliminated were: 99.0% Haemonchus sp.; 99.7% Cooperia sp.; 73.2% Trichostrongylus axei; 96.6% Bunostomum phlebotomum; 82.3% Oesophagostomum radiatum; and 100.0% Trichuris discolor. Based on the results obtained we may conclude: 1. A "pour-on" dose of 16 mg/kg has no anthelmintic value. 2. A "pour-on" dose of 48 mg/kg gives a better result but should not be recommended as anthelmintic. 3. An oral dose of 40 mg/kg gives the best results as anthelmintic against gastrointestinal nematodes. This dosage may be recommended for use of Ruelene 8-DP as an anthelmintic for cattle. 4. Further research must be conducted using the "pour-on" method to determine the proper dosage of Ruelene 8-DP.